2004
DOI: 10.1038/sj.npp.1300376
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Olanzapine and Haloperidol Differ on the Mouse N1 Auditory Evoked Potential

Abstract: Auditory evoked potentials have been used in a variety of animal models to assess information-processing impairments in schizophrenia. Previous mouse models have primarily employed a paired click paradigm to assess the transient measures of auditory gating. The current study uses stimulus trains at varied interstimulus intervals (ISI) between 0.25 and 8 s in mice to assess the effects of chronic olanzapine and haloperidol on auditory processing. Data indicate that olanzapine increases the amplitude of the N40,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 44 publications
4
58
1
Order By: Relevance
“…The electrode pedestal was secured to the skull using dental cement and Super Glue. All surgical procedures were consistent with previously published descriptions , Connolly et al, 2004, Maxwell et al, 2004a, Maxwell et al, 2004b, Siegel et al, 2005, Metzger et al, 2006.…”
Section: Surgerysupporting
confidence: 57%
See 2 more Smart Citations
“…The electrode pedestal was secured to the skull using dental cement and Super Glue. All surgical procedures were consistent with previously published descriptions , Connolly et al, 2004, Maxwell et al, 2004a, Maxwell et al, 2004b, Siegel et al, 2005, Metzger et al, 2006.…”
Section: Surgerysupporting
confidence: 57%
“…In fact, a recent study on the effects of nicotine on ERP components demonstrated opposite effects of nicotine on the P20 and N40 amplitudes in mice with nicotine increasing P20 amplitude and decreasing N40 amplitude (Metzger et al, 2006). We believe the mouse P20 and N40 to be analogous to the human P50 and N100 respectively based on previous research in our lab and others , Connolly et al, 2004, Maxwell et al, 2004a, Maxwell et al, 2004b, Umbricht et al, 2004, Siegel et al, 2005, Metzger et al, 2006. Thus, we have chosen to analyze the components independently in this study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our initial hypothesis to find a similar profile in the NR1 mutant mice was based on studies in rats, non-human primates and healthy volunteers, in which such a profile was reproduced by acute application of NMDAR antagonists, pointing to a possible involvement of the NMDAR in this deficit (Javitt et al, 2000a;Ehlers et al, 1992;Umbricht et al, 2004a). Furthermore, previous studies have shown that the mouse AEP peaks P1, N1, and P2 display refractory curves comparable to their putative human correlates (P1, N1, P2) (Umbricht et al, 2004b;Maxwell et al, 2004). Also, in two mouse studies that investigated the effects of pharmacological NMDAR blockade P1 was increased and N1 changed dependent on mouse strain (Maxwell et al, 2006;Connolly et al, 2004).…”
Section: Aep Peak Refractorinessmentioning
confidence: 72%
“…Early auditory sensory processing deficits in NR1 mutants S Bickel et al schizophrenia, and (2) the P1 and N1 peaks in mice do not represent the associate human peaks although the available evidence speaks against that (Umbricht et al, 2004b;Maxwell et al, 2004).…”
Section: Aep Peak Refractorinessmentioning
confidence: 99%